Greening for comfort: how planting design shapes user experience at Esplanade Park Kuantan - Syed Abu @ Syed Anuar, Sharifah Nur Alia Shafikah; Che Man, Shaibatul' Islamiah (2025)
Planting design is essential to leverage quality of life while promoting mental health and social interaction through well-designed green spaces. However, at this Esplanade Park Kuantan, the existing planting design seems to be ineffective in providing comfort to the users. Thus, this research aims to investigate the effect of planting design at Esplanade Park Kuantan in enhancing comfort and experience for user. The result of this study assesses to identify the most key planting elements that enhance comfort and satisfaction. Besides, to evaluate the planting design at Esplanade Park in influencing users' comfort, satisfaction, and overall users’ experience in mental well-being, particularly through promoting relaxation and fostering a sense of calm. The study employs site observations and questionnaire survey by 33 respondents through a convenience sampling method. The findings reveal that large shade trees, plant diversity, and thoughtful plant arrangements significantly contribute to the park’s aesthetic appeal and functional comfort. Most respondents prioritize shade provision, particularly for activities like strolling, exercising, and playing in the playground, while also recognizing the calming effect of greenery on their time spent in the park. The research emphasizes the need for ongoing improvements to the park's planting design to better meet user preferences and foster a more enjoyable, relaxing, and community-oriented environment.